IMPEDANCE-TO-DIGITAL CONVERTER, IMPEDANCE-TO-DIGITAL CONVERTING DEVICE, AND METHOD FOR ADJUSTMENT OF IMPEDANCE-TO-DIGITAL CONVERTING DEVICE - Jin-Chern CHIOU; Shun-Hsi HSU (My University, 2017)
An impedance-to-digital converter is provided. A sensible impedance range of the impedance-to-digital converter is adjustable by changing magnitudes of signals inputted thereto.